Analisa Pengaruh Pengangguran dan Indeks Pembangunan Manusia (IPM) Terhadap Tingkat Kemiskinan di Provinsi Aceh Tahun 2018-2022 - Thesia, Jesslyn; Tanjung, Ahmad Albar; Sukardi, Sukardi (Ekonomis: Journal of Economics and Business, 2024)
The aim of this paper is to find out the unemployment and the human development index effects on poverty in Aceh. The source of this report is secondary data obtained from BPS from 2018 to 2022. The estimation method used is Random Effect Model (REM). The results of this paper indicate that unemployment has a positive and significant impact on poverty and human development index does not affect poverty.